2023
DOI: 10.1245/s10434-023-13498-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of Laparoscopic Surgery with Improved Perioperative and Survival Outcomes in Patients with Resectable Intrahepatic Cholangiocarcinoma: A Systematic Review and Meta-Analysis from Propensity-Score Matched Studies

Abstract: Background Recent studies have associated laparoscopic surgery with better overall survival (OS) in patients with hepatocellular carcinoma (HCC) and colorectal liver metastasis (CRLM). The potential benefits of laparoscopic liver resection (LLR) over open liver resection (OLR) have not been demonstrated in patients with intrahepatic cholangiocarcinoma (iCC). Methods A systematic review of the PubMed, EMBASE, and Web of Science databases was performed to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Previous research has already associated laparoscopic approach to superior intraoperative, postoperative, and survival outcomes compared with open surgery in patients with colorectal liver metastases, intrahepatic cholangiocarcinoma, and HCC with Child-Pugh A and B cirrhosis. [38][39][40][41] The benefits of MILR in cirrhotic patients include better preservation of perihepatic collateral vessels, the supportive effect of pneumoperitoneum, reduced intraoperative blood loss, lower transfusion requirements, and limited nonsensory fluid loss. These advantages have shown a positive impact, reducing mortality and postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has already associated laparoscopic approach to superior intraoperative, postoperative, and survival outcomes compared with open surgery in patients with colorectal liver metastases, intrahepatic cholangiocarcinoma, and HCC with Child-Pugh A and B cirrhosis. [38][39][40][41] The benefits of MILR in cirrhotic patients include better preservation of perihepatic collateral vessels, the supportive effect of pneumoperitoneum, reduced intraoperative blood loss, lower transfusion requirements, and limited nonsensory fluid loss. These advantages have shown a positive impact, reducing mortality and postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we used stratified Cox models to adjust for inter-study heterogeneity by allowing patients from a given study to assume a baseline hazard unique to that study [ 23 ]. The Grambsch-Therneau tests for nonzero slope with a plotted scaled Schoenfeld residuals were applied to identify violations of the proportionality assumption of Cox regression models [ 24 ]. In addition, differences in survival outcomes between the LG and OG groups were also assessed via RMST, which can provide a robust estimation of survival at different cut-off time points in the presence of proportionality violation [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis conducted by Aliseda et al [70] reported interesting data related to laparoscopic resection for iCCA compared to open resection.…”
Section: Minimally Invasive Surgerymentioning
confidence: 99%